Investor Sentiments and Emergence of Tier II City Pune as Startup Destination - Palkar, Apoorva (AMC Indian Journal of Entrepreneurship, 2022)
Pune has 3200 startups and has produced few Unicorns. The growth of startups in any given region is an outcome of business growth of the startups and the investments that the startups attract from various sources of funding. Six startups have a valuation for more than USD 1 Billion and have joined the unicorn club with investments coming from Indian and overseas investors. 21 sectors have emerged as prominent ones where the startups have received funding at various stages namely, Angel funding, seed, pre-seed, venture funding, series A,B,C,D while unicorns have gone to series F. Large number of deals were seen in the third and fourth quarter of the year making Pune as the preferred destination of startups and investors.